The AI playbook mastering the rare art of machine learning deployment - Siegel, Eric 1968- (Cambridge, Massachusetts The MIT Press, 2024)
"A playbook for bridging business and data science worlds to effectively execute machine learning projects in business"--
Includes bibliographical references and index.
Keywords: Machine learning; Business -- Data processing